1993
DOI: 10.1095/biolreprod49.3.507
|View full text |Cite
|
Sign up to set email alerts
|

Function of Uterine and Blood-Derived Polymorphonuclear Neutrophils in Mares Susceptible and Resistant to Chronic Uterine Infection: Phagocytosis and Chemotaxis1

Abstract: In vitro phagocytosis and chemotaxis of uterine and blood-derived polymorphonuclear neutrophils (PMNs) were compared in mares with different resistance to chronic uterine infection (CUI). Both the primary in vitro function of PMNs and the role of uterine environmental factors on PMN function were investigated. The uteri of mares susceptible to (n = 6) and resistant to CUI (n = 5) were inoculated with 5 x 10(6) Streptococcus zooepidemicus when the mares were in estrus. Uterine secretions in addition to uterine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 16 publications
1
42
0
1
Order By: Relevance
“…Troedsson et al (1993) observed that uterine activity is higher on the first 6 hours after breeding, and is maintained until 19 hours in resistant mares, but decreases to basal levels during this period in susceptible mares. According to Frean et al (1997), Yallampalli et al (1994) and Alghamdi et al (2005), the presence of nitric oxide promotes uterine relaxation and may contribute to a decrease in uterine clearance.…”
Section: Discussionmentioning
confidence: 90%
“…Troedsson et al (1993) observed that uterine activity is higher on the first 6 hours after breeding, and is maintained until 19 hours in resistant mares, but decreases to basal levels during this period in susceptible mares. According to Frean et al (1997), Yallampalli et al (1994) and Alghamdi et al (2005), the presence of nitric oxide promotes uterine relaxation and may contribute to a decrease in uterine clearance.…”
Section: Discussionmentioning
confidence: 90%
“…At the time of semen collection, blood was collected from a healthy mare and PMNs were isolated as previously described (Troedsson et al 1993). Briefly, heparinized blood was subjected to centrifugation, the buffy coat was layered over a lymphocyte separation medium (Litton Bionetics, Kensington, MD, USA) and the PMNs were recovered from the buffy coat.…”
Section: Preparation Of Pmnsmentioning
confidence: 99%
“…Five mares were inseminated with 1 £ 10 9 spermatozoa with at least 50% progressive motility and uterine secretion samples were collected 12 h later using cotton tampons as previously described (Troedsson et al 1993. The tampon was recovered by the use of a vaginal speculum and placed in a small, sterilized plastic bag to prevent evaporation.…”
Section: Uterine Secretionsmentioning
confidence: 99%
“…Uterine defense mechanisms: Polymorphonuclear neutrophils (PMNs) are present in the uterine lumen within 30 minutes after mating (Katila,7995). Both bacterta and spermatozoa stimulate PMN-chemotaxis into the uterus (B/ue et al, 1984;Pycock and Allen, 1988;Troedsson et al, 1993a;Troedsson et al, 1995a) . Several mediators, including ?GFza are released during the course of the inflammation (Schalm, 1986).…”
Section: Pathophysiology Of Mating-induced Endometritismentioning
confidence: 99%